Do luto à luta: posvenção e resiliência em sobreviventes enlutados pelo suicídio - Burlamaque, Alexandra Verardi (2024)
Death leads to the unknown and, when it comes to death by suicide, it is known that several people will be affected due to the pain of grief, the abrupt and violent aspect that involves this type of death and the social stigma. Having a potentially complicated grief given the great psychic energy that is required to face this grief. The study aims to understand which experiences, within the scope of postvention, contribute to resilience in coping with loss. The specific objectives are to understand the psychosocial effects of suicide on the bereaved family and the grieving process experienced; understand the main strategies used by families to establish or not establish resilience and what are or could be the aspects that reinforce resilience in the grieving process; contribute within the scope of public policies, with indications of actions to postvention aimed at promoting care for bereaved survivors. This is a qualitative, descriptive and field research, developed through the application of semi-tructured interviews with eight family members of people who committed suicide, all of them belonging to the person's nuclear family (parents, siblings, spouse, children), over 18 years old. For the carrying out the interviews, two meetings were held, via online platform, with each participant. The interview followed a script divided into the following axes: understanding the family structure before and after the loss; coping and resilience; postvention. The research project was approved by the Ethics Committee and the ethical principles of privacy, secrecy and confidentiality were respected. The statements were recorded with the consent of the research participants. The analysis and interpretation of the data obtained was inspired by the content analysis method, proposed by Bardin (1977). The research results are presented, in this dissertation, in the form of two scientific productions. The first of them is entitled "Postvention with survivors bereaved by suicide: gaps in Brazilian reality" and the second is titled "The unnameable: representations of death by suicide". It was observed that death by suicide reverberates in different ways and intensities in the lives of bereaved survivors who identify in their experiences the rupture with the world previously known, which causes intense suffering and existential conflicts. Furthermore, it was identified that the experience of grief, in the case of suicide, is permeated by nuances of blame, questioning, judgment and emotional ambivalence related to what happened. Therefore, the existence of social judgment and society's lack of preparation for welcoming the bereaved keep them away from the possibilities of interventions linked to postvention, which are still little promoted in Brazil and in public policies. Finally, those interviewed who were able to access spaces of care and validation went to support groups created by the survivors themselves and still little publicized. It is concluded that postvention strategies, such as social acceptance, education for death by suicide and effective and welcoming interventions by the formal care network, have significant strength in increasing and promoting resilience, both individual and family.